ANALISIS PERENCANAAN DAN PENGENDALIAN PRODUKSI INJECTION PART NEW MODEL PAJERO SPORT 20 MY DI PT. SHIN SAM PLUS INDUSTRY KARAWANG - Supriatna, Yana; Hersusetiyati, Hersusetiyati; Priadi, Muhammad Dadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study is to analyze how planning, controlling and project recommendations for making injection components for the New Model Pajero Sport 20 MY car at PT. Shin Sam Plus Industry in fulfilling customer demand Using a qualitative approach, data collection techniques through interviews and observations, compiling research instruments and conducting analysis and checking the validity of the data, the object of research is in the Division of Production Planning and Inventory Control (PPIC) Sukaluyu, Telukjambe Timur, Kabupaten Karawang. The results of the research on project planning for the manufacture of injection components for the New Model Pajero Sport 20 MY car at PT. Shin Sam Plus Industry, in fulfilling customer requests, performs machine check sheets, for example 5 (five) minutes before starting the process is checked so that when production hours are running well there are no obstacles whatsoever that impact Stop production. Checking the raw materials, the plan has been distributed H-1 or according to company policy, all according to the plan that has been set, if there is a revision, it is not immediately revised. Control is carried out indirectly, meaning that the capacity is insufficient and a back up plan is needed, namely by subcontracting the product to the vendor and the need for a feasibility study with an audit so that it can meet the requirements requested by the customer. Control based on certain conditions is by means of the need for a contingency plan in all aspects so as to meet customer demand when there are internal or external abnormal conditions. PPC also monitors the materials required for production. Convey as detailed information as possible from internal and customers. Analyze the data obtained. Display data and discuss and then monitor production forecasts that have been made. Taken from the forest data sent by the customer and calculated for the Reject Ratio, Monitor consumption consumption, production and standard consumption data from engineering. Proposals related to solutions for fulfilling customer requests that can be provided to Management, so as to increase company profits, Request to the Dept. Engineering to be able to review consumption standards at least once a month to avoid differences in consumption usage. Then the addition of equipment/tools used by the process (such as packaging, jigs, trolly, etc.), agenda for routine review between departments. POs received from customers must enter the maximum AKR at the end of the month or on the 20-25th to carry out cost calculations and update production capacity, recommendations for employees of PT. Shin Sam Plus Industries. In order to be more intentional about checking raw materials, this is done to ensure that production does not stop due to waiting for material or not available so that productivity is constrained.